Detection of the actinide Th in an r-process-enhanced star with accretion origin - Xing, Qianfan; Zhao, Gang; Aoki, Wako; Li, Haining; Zhao, Jingkun; Matsuno, Tadafumi; Suda, Takuma (The astrophysical journal, 2024)
The thorium and six second-peak r-process element (56 ≤ Z ≤ 72) abundances are determined for the α-poor star LAMOST J1124+4535 based on a high-resolution spectrum obtained with the High Dispersion Spectrograph on the Subaru Telescope. The age of J1124+4535 is 11.3 ± 4.4 Gyr using thorium and other r-process element abundances. J1124+4535 is confirmed to be a Galactic halo metal-poor ([Fe/H] = −1.27 ± 0.1) star with extreme r-process element overabundance ([Eu/Fe] = 1.13 ± 0.08) and α element deficiency ([Mg/Fe] = −0.31 ± 0.09) by the LAMOST-Subaru project. Along with the subsolar α-to-iron ratios (e.g., [Mg/Fe], [Si/Fe], [Ca/Fe]), the relatively low abundances of Na, Cr, Ni, and Zn in J1124+4535 show a significant departure from the general trends of the Galactic halo but are in good agreement with those of dwarf galaxies. The chemical abundances and kinematics of J1124+4535 suggest it was formed in the late stage of star formation in a dwarf galaxy that has been disrupted by the Milky Way. The star formation of its progenitor dwarf galaxy lasted more than 2 Gyr and has been affected by a rare r-process event before the occurrence of accretion event.
Gesehen am 27.09.2024